Enhancing Reading Skills of Surah Al-Zalzalah: A Makharijul Huruf Study at Nurul Hasanah TPQ - Putri, Annindita Hartono (AJIS: Academic Journal of Islamic Studies, 2024)
This research aims to analyze the role of teaching Makharijul Huruf in enhancing Quranic reading skills, particularly focusing on Surah Al-Zalzalah, at the Nurul Hasanah Quranic Education Park in Jakarta. The research method employed is a qualitative approach with a case study, involving observation, interviews, and documentation. The results indicate that understanding Makharijul Huruf serves as the fundamental basis in the science of Tajwid, influencing Tajwid aspects and forming a strong foundation for correct Quranic reading. At Nurul Hasanah Quranic Education Park in Jakarta, the teaching of Makharijul Huruf incorporates kinesthetic approaches, auditory instructions, and interactive games. Evaluation involves memorization of targets and materials, recognizing that each child's reading ability may differ. Despite the positive impact of teaching Makharijul Huruf, difficulties in pronouncing certain letters such as 'ذ', 'ز', 'ض', 'ص', 'ح', and 'ث' were identified. Continuous improvement is necessary to ensure that every student can overcome pronunciation difficulties, enhance Quranic reading abilities, and support the development of effective teaching methods at the Quranic Education Park. This research is expected to contribute to the development of relevant teaching methods to improve Quranic reading skills in the Quranic Education Park.